(untitled) (Journal of Geography and Environmental Management, 2021)
In the work, according to the scenarios of climatologists, it is shown that the absence of changes in the amount of precipitation and an increase in the average annual surface air temperature on land will contribute to aridization and desertification of the territory of Kazakhstan under conditions of global warming. In this regard, climatic desertification will contribute to the displacement of the zone of insufficient moisture and an increase in the zone of desert and semi-desert regions. A forecast of a decrease in the yield of grain crops in these conditions is presented, which is a threat to the environmental and food security of Kazakhstan. The aim of the research is to analyze the impact of climate change on agricultural production and the state of water resources in the Republic of Kazakhstan and to develop an adaptive model of the impact of climate change on natural and economic systems. The analysis of the state of water resources as the most vulnerable component for the country under changing climatic conditions is presented. It is shown that under these conditions, adaptation measures are carried out in the Republic aimed at reducing climatic risks and at deriving potential benefits from climate change. We have proposed an adaptive model of the impact of climate change on natural and economic systems, which is based on the methods of mathematical statistics and probabilistic analysis. The levels of adaptation are interpreted in accordance with the index: with an increase in the indicator, the degree of influence on natural and economic systems also increases. The model has a high potential for use in predicting climate change within geographically limited natural and economic systems. The proposed recommendations for adaptation to climate change can find application in the development of state programs for the management of natural and climatic risks.